Trust in Classroom-as-Organization Simulations: Parallel Experiences of Participants and Facilitators. (June 2021) - Levesque, Laurie L.
Background: Asclassroom-as-organization (CAO)simulations unfold within corporate or higher education classrooms, novice facilitators and their participants experience uncertainty in the absence of familiar and implicit sources oftrust . Initialtrust derived from the context, simulation, peers, and one's self wanes as awareness dawns regarding the magnitude of difference between CAO and typical classrooms. New sources oftrust arise from sharedsensemaking about unfamiliar roles and interactions, growing confidence in redistributed responsibilities and authority, an environment characterized by psychological safety, feedback, and behavioral experimentation modeled upon the experientiallearning cycle (Kolb, 1976 ). Purpose: This article examines the parallel experiences of participants andnovice facilitators as they initially losetrust in CAO simulations and those involved, and discover new sources oftrust related to the simulation design. Using first- and second-hand experiences and extant literatures on trust and teaching andlearning, the erosion of initial trust is explored, as well as how CAO simulation design principles foster new sources of emergenttrust . Conclusion: Understanding the ebb and flow of participants' trust in CAO simulations allows for targetedfacilitation and coaching.Novice facilitators who examine how their own trust experiences parallel those of participants gain insight into interventions and empathy into the participant experience within this fully-experientiallearning environment. Empirical research is needed to examine the mechanisms oftrust loss and rebuilding in CAO simulations in relation to the enactment of unfamiliar roles, routines, and responsibilities.